Proteomic analysis of peptides tagged with dimedone and related probes. (20th March 2014) - Martínez‐Acedo, Pablo; Gupta, Vinayak; Carroll, Kate S.
<x xml:space="preserve">Abstract</x> Owing to its labile nature, a new role for cysteine sulfenic acid (–SOH) modification has emerged. This oxidative modification modulates protein function by acting as a redox switch during cellular signaling. The identification of proteins that undergo this modification represents a methodological challenge, and its resolution remains a matter of current interest. The development of strategies to chemically modify cysteinyl‐containing peptides for liquid chromatography–tandem mass spectrometry (LC‐MS/MS) analysis has increased significantly within the past decade. The method of choice to selectively label sulfenic acid is based on the use of dimedone or its derivatives. For these chemical probes to be effective on a proteome‐wide level, their reactivity toward –SOH must be high to ensure reaction completion. In addition, the presence of an adduct should not interfere with electrospray ionization, the efficiency of induced dissociation in MS/MS experiments or with the identification of Cys‐modified peptides by automated database searching algorithms. Herein, we employ a targeted proteomics approach to study the electrospray ionization and fragmentation effects of different –SOH specific probes and compared them to commonly used alkylating agents. We then extend our study to a whole proteome extract using shotgun proteomic approaches. These experiments enable us to demonstrate that dimedone adducts do not interfere with electrospray by suppressing the ionization nor impede product ion assignment by automated search engines, which detect a + 138 Da increase from unmodified peptides. Collectively, these results suggest that dimedone can be a powerful tool to identify sulfenic acid modifications by high‐throughput shotgun proteomics of a whole proteome. Copyright © 2014 John Wiley & Sons, Ltd.